2021
DOI: 10.1016/j.jid.2020.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Perturbations in Patients with Hidradenitis Suppurativa: A Case Series

Abstract: JZ, et al. Exome sequencing of desmoplastic melanoma identifies recurrent NFKBIE promoter mutations and diverse activating mutations in the MAPK pathway. Nat Genet 2015;47:1194e9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 17 publications
2
28
1
Order By: Relevance
“…99 In a small pilot study, Kam and colleagues sampled the gut microbiome from three HS patients and three healthy controls. 100 A significant decrease in α-diversity (a measure of the differences within a community) and significant decrease in the abundance of Firmicutes were noted in HS patients compared with controls. 100 In a separate study by Lam and colleagues, the gut microbiome was investigated in a larger patient cohort, including 17 HS patients and 20 healthy controls.…”
Section: The Gut Microbiome Of Hsmentioning
confidence: 98%
See 1 more Smart Citation
“…99 In a small pilot study, Kam and colleagues sampled the gut microbiome from three HS patients and three healthy controls. 100 A significant decrease in α-diversity (a measure of the differences within a community) and significant decrease in the abundance of Firmicutes were noted in HS patients compared with controls. 100 In a separate study by Lam and colleagues, the gut microbiome was investigated in a larger patient cohort, including 17 HS patients and 20 healthy controls.…”
Section: The Gut Microbiome Of Hsmentioning
confidence: 98%
“…100 A significant decrease in α-diversity (a measure of the differences within a community) and significant decrease in the abundance of Firmicutes were noted in HS patients compared with controls. 100 In a separate study by Lam and colleagues, the gut microbiome was investigated in a larger patient cohort, including 17 HS patients and 20 healthy controls. 101 In contrast to Kam et al, this study did not find any alterations in α-diversity or Firmicutes abundance in HS patients.…”
Section: The Gut Microbiome Of Hsmentioning
confidence: 98%
“…Only two studies were identified which investigated the gastrointestinal microbiome in HS. [40]. However, this study was very small, with only three participants each in the HS and control groups.…”
Section: The Main Findingsmentioning
confidence: 88%
“…1 Furthermore, the gut-skin axis and in particular the link between the gut microbiome (and its metabolic output) and inflammatory cutaneous diseases like HS is becoming increasingly apparent, and warrants study in the context of HS. 162,163 For instance, reduced short chain fatty acid (SCFA) output from the gut microbiome has long been linked with IBD and associated inflammation, and can be directly mapped to immunological effects on T-cell polarization and macrophage function. [164][165][166] Aside from bacteria, other microorganisms which form part of the skin microbiome have also been linked with complications in HS.…”
Section: The S K In Microb I Ome " Barrier " In Hsmentioning
confidence: 99%